Symposium 11: ’How it was for me…’ First steps on our Learners’ Journeys through HE - Jefferies, A. L.; Hyde, R. S.; Bullen, P. R. (Proceedings of the International Conference on Networked Learning, 2008)
The JISC funded STROLL project set out to document and research into learners’ own views of their experiences of learning within what is seen as a technology-rich environment and to consider a range of learners’ experiences of learning recorded during their’journeys’ at the University of Hertfordshire (UH) and Hertford Regional College (HRC). Over thirty undergraduates from a diverse set of backgrounds have been recruited to the project as volunteers and reflect the university’s wide diversity of intake in race, age, gender and nationality. In May 2007 the STROLL team invited students to spend a pilot week recording their learning experiences. Creating their own video or audio diaries with webcams or camcorders or using digital voice recorders, the students recorded their answers to a series of questions. Do you enjoy using technology for learning or leisure? Do you have any difficulties using technology in every day life and in your studying? What would make e.learning technology easier to use? Have you used any social network technologies this week? How do you use them? What do you like/dislike about them? How can your lecturers use technology (including StudyNet) even better to improve your learning? What tricks are they missing or what ideas could they use? Further diaries are being recorded in October 2007 and in March and October 2008, with a variation of the questions each time. The project report will provide a set of longitudinal experiences, the ’learners’ journeys’, showing the use that students make of e-learning tools such as the university’s own MLE (StudyNet) and the pervasiveness of technology for learning and leisure in their everyday lives. The project team will bring to the symposium examples of the early results from the first two sets of diaries, including some sample video clips of the students’ reflections in response to the questions identified above. These indicate an enthusiasm for using technology across the student group both for learning and leisure and a widespread use of social networking tools. These are broadly in line with findings from the Phase 1 outcomes. The symposium will also be an opportunity to discuss research methodologies as they emerge across the consortium of projects. There has been relatively little research into the use of video diaries to capture student reflection on learning, although there are examples of their prior use in medical research for patients monitoring their own conditions. A qualitative approach to the analysis of the data has been followed. Transcripts of the audio and video files were produced, themes from the data were recorded and the student transcripts subsequently colour coded according to the students’ comments on the key questions asked. This allowed a quick comparison of data between the different sets of student reflections. Later on NVivo was used to support and record the tracking of the large quantities of data. Short telephone interviews were used to follow up the individual students after their data had been transcribed. Some quantitative data was also gathered to record the backgrounds and programmes of study and to provide an audit trail for the project. This has been analysed using SPSS. The paper and presentation discuss the practicalities of organising video diaries as a means of capturing a rich amount of data and the methods used to analyse them, given the quantities of data available as well as indicative answers to the main research questions.